2010
DOI: 10.1159/000320186
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Vinorelbine and Capecitabine Combination Therapy in Chinese Patients with Metastatic Breast Cancer Pretreated with Anthracyclines and Taxanes

Abstract: Aims: This phase II study prospectively evaluated the feasibility of vinorelbine in combination with capecitabine in Chinese patients with metastatic breast cancer (MBC) pretreated with anthracyclines and taxanes. Methods: Vinorelbine (25 mg/m2 intravenous infusion on days 1 and 8) and capecitabine (1,000 mg/m2 b.i.d., days 1–14) were administered to eligible MBC patients previously treated with anthracyclines and taxanes every 3 weeks for up to 6 cycles, until disease progression or unac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The response rate of capecitabine plus docetaxel or vinorelbine was about 42-60%, and the median PFS was 6.1-9.3 months [16,17,18]. But data about capecitabine in TNBC patients are limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The response rate of capecitabine plus docetaxel or vinorelbine was about 42-60%, and the median PFS was 6.1-9.3 months [16,17,18]. But data about capecitabine in TNBC patients are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of grade 3/4 neutropenia, nausea/vomiting and HFS was 33.3, 4, 16% in the standard dose group (capecitabine 1,250 mg/m 2 , twice daily) and 22.2, 7.4, 11.1% in the low dose group (capecitabine 825 mg/m 2 twice daily). Trials [16,29] evaluating vinorelbine plus capecitabine reported that the incidence of grade 3/4 neutropenia, nausea/vomiting and HFS varied from 13 to 45, 0 to 5 and 0 to 3%. In our NX group, the incidence of grade 3/4 HFS seemed to be higher (11.1%) than those reported in the literature, and the reasons are still to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This regimen had significant toxicity, with most patients experiencing severe or life-threatening hematologic, renal or infectious complications [121]. The oral agent capecitabine is now an established therapy for MBC, with activity even at low doses, especially when combined with vinorelbine [122,123,124]. The combination of cisplatin with capecitabine was evaluated in two trials recruiting patients with MBC resistant to anthracyclines and taxanes.…”
Section: Experience With Combination Chemotherapymentioning
confidence: 99%
“…Capecitabine is a highly effective oral fluoropyrimidine that is converted to 5-fluorouracil in vivo through a 3-step enzymatic process including thymidine phosphorylase. Docetaxel and vinorelbine have been found to increase the level of thymidine phosphorylase in tumor tissue, leading to a potential mechanism for a synergistic effect [6]. Previously, we conducted a phase II study of capecitabine and docetaxel followed by fluorouracil/epirubicin/cyclophosphamide (FEC) as preoperative treatment in women with stage II/III breast cancer, because capecitabine (X) and docetaxel (T) have demonstrated a synergistic effect and the sequential combination of anthracycline and taxane is a standard of care in the preoperative setting as well as in the adjuvant setting [7].…”
Section: Introductionmentioning
confidence: 99%